Factores asociados a la práctica de la citología de cuello uterino, en mujeres desplazadas y población receptora en un asentamiento en Antioquia, Colombia, 2011 (2013)
ABSTRACT: To characterize the socio-economic, demographic and health insurance factors associated with Pap smears among displaced and host population in the “Altos de Oriente” settlement, located in Bello, Colombia in 2011. Methodology: we conducted a secondary data analysis on the cross-sectional study entitled "Historical and socio-demographic description of the settlement Altos de Oriente.” The survey inquired about the date of the last Pap smear, health insurance, and socioeconomic and demographic variables. We performed a descriptive analysis and built logistic regression models. Results: both the displaced and host women from the settlement have low education, low income, and are mostly single mothers. The factors associated with not having a recent Pap smear were: being 41 to 49 years old, not using family planning methods, being unemployed and having only elementary school education or no education at all. Conclusions: efforts to increase coverage of Pap smear services in this group of displaced and host individuals should focus on women aged 41 to 49, who are housewives with a low education level.